Vorticity Fields on Flow with Vortex System - Yulistiyanto, Bambang (Institut Teknologi Bandung, 2009)
Abstract. The flow around a circular cylinder mounted normal to the channel bed is essentially a three-dimensional one. The flow upstream undergoes a separation of the turbulent boundary layer and rolls up to form a flow system, known as horseshoe vortex, which is swept around the cylinder. This vortex system plays an important role, if the bed material is movable. The shear stress of the vortex system is responsible to the bed erosion. The shear stress depends on the velocity gradient, may be presented as the vorticity. This study is done to gain a better understanding of the vorticity around a cylinder, especially where the system of vortices exist. Flow measurements were used to study the vorticity fields on flow with a horse-shoe vortex system around a pile. The velocity vector plots show the presence of a primary vortex upstream of the cylinder. Based on these velocity vectors, the vorticity can be analyzed by using central finite difference approximations. Results of the vorticity calculation are presented as the vorticity contours. Results of study show the greatest value of the positive-vorticity on the horse-shoe vortex system is in the plane upstream of cylinder. This value decreases in the planes downstream, attaining the lowest value in the plane downstream, where the wake vortex established. The strength of the positive vorticity increases at larger Reynolds number. Underneath the field of positive vorticity, stretching around the cylinder, it appears a field of negative vorticity. This negative vorticity near the bed is high in front of the cylinder, proportional to the bed shear stress, which is responsible to the development of local scour at the movable bed. The line of zero vorticity is plotted originated at the bed, being as the separation point. It is also concluded that the maximum positive-vorticity is not necessary coincided with the center of the vortex.Abstrak. Pola aliran di sekitar silinder bulat yang dipasang tegak lurus dasar saluran merupakan aliran tiga dimensi Aliran di hulu silinder membentuk separasi pada lapis batas turbulen, membangkitkan terbentuknya pusaran tapal-kuda yang mengelilingi silinder. Sistem pusaran ini mempunyai peranan penting jika material dasar mudah bergerak. Tegangan geser pada sistem pusaran akan menyebabkan terbentuknya erosi lokal. Besarnya tegangan geser bergantung pada perbedaan kecepatan, yang dapat dipresentasikan dengan nilai vortisitasnya. Studi ini bertujuan untuk mendapatkan pemahaman yang lebih baik tentang vortisitas di sekitar silinder, terutama di lokasi dimana terbentuk system vortex. Data hasil pengukuran kecepatan aliran dipakai untuk mempelajari system vortisitas pada aliran dengan sistem pusaran di sekitar pilar. Gambar vektor kecepatan di sekitar pilar silinder memperlihatkan keberadaan pusaran utama di depan silinder. Berdasarkan vector kecepatan tersebut, dapat dianalisis vortisitasnya dengan menggunakan metode beda hingga. Hasil hitungan vortisitas digambarkan dalam bentuk kontur vortisitas. Hasil studi menunjukkan nilai maksimum dari vortisitas positif (searah jarum jam) dari sistem pusaran tapal kuda adalah pada bidang simetri di hulu silinder. Nilai vortisitas tersebut menurun, mencapai nilai minimum di hilir silinder. Besarnya vortisitas positif meningkat pada angka Reynold yang lebih tinggi. Di bawah bidang vortisitas positif, diperlihatkan terbentuknya system vortisitas negatif. Vortisitas negative di dekat dasar di depan silinder mempunyai nilai yang besar, proporsional dengan nilai tegangan geser di dasar, yang bertanggungjawab pada terbentuknya erosi lokal pada saluran dengan dasar bergerak. Garis yang memberikan nilai vortisitas sama dengan nol, merupakan garis separasi antara vortisitas positif dan negative. Dari hasil kajian juga disimpulkan bahwa posisi dari vortisitas positif maksimum tidak selalu berimpit dengan pusat pusaran tapal kuda.